2003
DOI: 10.1152/japplphysiol.00598.2002
|View full text |Cite
|
Sign up to set email alerts
|

Extended high-frequency partial liquid ventilation in lung injury: gas exchange, injury quantification, and vapor loss

Abstract: High-frequency oscillatory ventilation with perflubron (PFB) reportedly improves pulmonary mechanics and gas exchange and attenuates lung injury. We explored PFB evaporative loss kinetics, intrapulmonary PFB distribution, and dosing strategies during 15 h of high-frequency oscillation (HFO)-partial liquid ventilation (PLV). After saline lavage lung injury, 15 swine were rescued with high-frequency oscillatory ventilation (n = 5), or in addition received 10 ml/kg PFB delivered to dependent lung [n = 5, PLV-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…Doctor et al (35) observed a significant reduction in atelectasis in a saline lavage-induced model of lung injury in swine treated with HFOV-PLV for 2 hrs after a 30-mL/kg dose of PFOB, in comparison with HFOV alone. The same investigators obtained similar findings in a subsequent study comparing two dosing strategies of HFOV-PLV (5 mL/kg in each the prone and supine position or 10 mL/kg in the supine position) and HFOV alone in a more severe, prolonged large animal model of injury (32). Smith et al (24) found that PLV with a conventional ventilator or PLV coupled with various high-frequency techniques (HFOV, jet, or flow interruption) resulted in attenuation of lung-injury scores in saline lavageinjured newborn piglets.…”
Section: Discussionmentioning
confidence: 52%
“…Doctor et al (35) observed a significant reduction in atelectasis in a saline lavage-induced model of lung injury in swine treated with HFOV-PLV for 2 hrs after a 30-mL/kg dose of PFOB, in comparison with HFOV alone. The same investigators obtained similar findings in a subsequent study comparing two dosing strategies of HFOV-PLV (5 mL/kg in each the prone and supine position or 10 mL/kg in the supine position) and HFOV alone in a more severe, prolonged large animal model of injury (32). Smith et al (24) found that PLV with a conventional ventilator or PLV coupled with various high-frequency techniques (HFOV, jet, or flow interruption) resulted in attenuation of lung-injury scores in saline lavageinjured newborn piglets.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, PFC associated recruitment of atelectatic alveoli [11], was also achieved in Persurf treated animals. In liquid ventilated animals atelectasis will re-appear after evaporation of PFC, since the underlying disturbances of pulmonary surfactant persist [41]. In contrast, the homogenous alveolar expansion should persist in Persurf treated animals after PFC evaporation since surfactant has been replaced.…”
Section: Discussionmentioning
confidence: 99%
“…By design, approximately half of the FRC in the HF-PLV1/2 group was liquid-filled at the start of treatment, and approximately 50% of that initial dose would still be present at 4 hrs, based on expected PFC evaporative loss under similar conditions (33,34). Two PFC dosing regimens were used to further evaluate the effect of PFC volume on outcome.…”
Section: Discussionmentioning
confidence: 99%